Success Rate of Combined Transcanalicular Diode Laser and Endoscopic Dacryocystorhinostomy in Patients of Nasolacrimal Duct Obstruction - Awan, Ammarah Ashraf; Naqvi, Syeda Alishba Zahra; Rafique, Aisha; Yasin, Ubaid Ullah; Butt, Waqas Rahim; Naqvi, Syed Abid Hassan (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the success rate of combined Endoscopic Dacryocystorhinostomy (DCR) and Transcanalicular Diode Laser DCR in patients with nasolacrimal duct obstruction.Study Design: Analytical cross-sectional study.Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from March 2024 to Mar 2025.Methodology: Patients presenting with epiphora and a positive regurgitation-on-pressure test were enrolled through convenience sampling. Pre-sac patency was assessed using lacrimal syringing, which confirmed complete nasolacrimal duct obstruction. All patients underwent combined Transcanalicular Diode Laser DCR and Endoscopic DCR performed as a simultaneous procedure. Outcomes were evaluated at a 6-month postoperative follow-up, assessing overall, anatomical, and functional success.Results: A total of 150 patients were included, with a mean age of 54.9±9.8 years (range: 28–76 years). The overall success rate was 92.0%, while anatomical and functional success rates were 96.0% and 91.3%, respectively (p=0.016). Functional pathology was the leading cause of failure, and lid laxity (22.7%) was significantly associated with functional failure (23.5% vs 4.3%, p